Rhythm & recall: EduBeatz for cognitive-friendly economics education - Harun, Hazalinda; Hasbullah, Nornajihah Nadia; Kamis, Rohaiza; Abidin, Mohd Isham; Awang, Amizatul Hawariah (2025)
EduBeatz offers an innovative approach to teaching business and economics by integrating music and rhythm to enhance memory and engagement. Traditional lecture-based methods often result in low knowledge retention, while active learning techniques, especially those using auditory and visual elements, can significantly improve learning outcomes. EduBeatz simplifies complex economic concepts into educational songs using familiar melodies and accessible lyrics, supporting learners with diverse cognitive needs, including short-term memory challenges and dyslexia. In this study, the researchers designed the lyrics and music by incorporating content from selected economics chapters, branding it as EduBeatz. To test the effectiveness of the lyrics and music, students were required to answer a questionnaire after listening to the song and lyrics. The study applies the Theory of Planned Behavior (TPB) to examine the intention to adopt music-based learning among 200 undergraduate students at Universiti Teknologi MARA (UiTM) Bandaraya Melaka. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results show that Attitude, Subjective Norm, and Perceived Behavioural Control significantly influence students’ intention, with Perceived Behavioural Control being the strongest predictor. Findings support EduBeatz as an effective and inclusive pedagogical tool with potential applications in classrooms, e-learning, and corporate training. By transforming theory into rhythm, EduBeatz makes learning more memorable, accessible, and enjoyable.